" … it's almost therapeutic, right? Because it's almost like that session that I never had": gay men's accounts of being a participant in HIV research. Issue 10 (2nd October 2016) - Grace, Daniel; Steinberg, Malcolm; Chown, Sarah A.; Jollimore, Jody; Parry, Robin; Gilbert, Mark
ABSTRACT: Limited research has explored how gay, bisexual and other men who have sex with men describe the impact of their involvement in HIV and sexual health research. We enrolled 166 gay and bisexual men who tested HIV-negative at a community sexual health clinic in Vancouver, British Columbia, into a year-long mixed methods study. Thirty-three of these participants who reported recent condomless anal intercourse were purposively recruited into an embedded qualitative study. Analysis revealed rich accounts of the self-described, interrelated impacts of study participation: (1) pride in contribution and community involvement (e.g., as a rationale for enrolment and an outcome of participation); (2) how one thinks about sexual behaviours and partnerships (e.g., encouraging reflection on the types and amount of sex they have had; in some cases the methods of quantitative data collection were said to have produced feelings of guilt or shame); and (3) experiencing research as a form of counselling (e.g., qualitative interviews were experienced as having a major therapeutic component to them). Our analysis underscores the importance of researchers being reflexive regarding how study participation in HIV research may impact participants, including unintended emotional and behavioural impacts.